University Characteristics as Factor Affecting the Creation of University Spin-Offs (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The university-spin off company is a specific but rather effective tool for the direct transfer of knowledge and new technology from academia into business. However, this seems to be still a not very common phenomenon in many European countries. The paper aims to compare the characteristics of universities in European countries based on empirical data for 2465 higher education institutions in Europe retrieved from European Tertiary Education Register database. We examined factors that could have a potential effect on the creation of university spin-off companies in Europe. In order to find these factors we applied logit and probit regression analysis. Our results strongly suggest that those universities which are neither strongly focused on a few fields of research, nor very broad in their focus are mostly less active in creating the university spin-off companies. The intensity of PhD study, the share of tuition fees as well as a number of foreign students seem to be factors affecting university spin-off activities.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.